2018
DOI: 10.1111/bdi.12642
|View full text |Cite
|
Sign up to set email alerts
|

Psychoeducation for psychiatric inpatients following remission of a manic episode in bipolar I disorder: A randomized controlled trial

Abstract: This preliminary evidence suggests that short, group-based psychoeducation benefits currently medicated inpatients following the remission of mania in bipolar I disorder. This intervention warrants further investigation, especially in other Chinese populations. If future studies confirm its benefits, group-based psychoeducation could be incorporated into routine psychiatric inpatient care for bipolar patients in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 36 publications
0
41
0
2
Order By: Relevance
“…PE delayed time to next bipolar episode only in patients with up to 7 previous episodes (Morriss et al 2016); however, PE was superior to peer support in the overall sample on time to next manic episode, acceptability (defined by number of attended sessions) and interpersonal function as assessed with the interpersonal domain of the Social Adjustment Scale (Morriss et al 2016). Along those lines, a short group PE (2 weeks, 8 × 40–60 min) showed improved recurrence prevention and clinical global functioning at 1 year in inpatients with remitted mania and few previous bipolar episodes (Chen et al 2018). Of note, limitations of this study are a sample of 90% females and the delivery of unstructured group meetings by nurses (PE by psychiatrists or clinical psychologists).…”
Section: Discussionmentioning
confidence: 98%
“…PE delayed time to next bipolar episode only in patients with up to 7 previous episodes (Morriss et al 2016); however, PE was superior to peer support in the overall sample on time to next manic episode, acceptability (defined by number of attended sessions) and interpersonal function as assessed with the interpersonal domain of the Social Adjustment Scale (Morriss et al 2016). Along those lines, a short group PE (2 weeks, 8 × 40–60 min) showed improved recurrence prevention and clinical global functioning at 1 year in inpatients with remitted mania and few previous bipolar episodes (Chen et al 2018). Of note, limitations of this study are a sample of 90% females and the delivery of unstructured group meetings by nurses (PE by psychiatrists or clinical psychologists).…”
Section: Discussionmentioning
confidence: 98%
“…Previous research has criticized the deficiency of China’s mental health services [35]. Psychological intervention is not usually available in general hospitals or psychiatric hospitals [36, 37], let alone in forensic psychiatric hospitals. We suggest that hospitals should provide better psychological interventions.…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent RCT showed fewer depressive and manic recurrences in the treatment group (Castle et al 2010 ). Eight sessions of group PE delivered during 2 weeks were superior to the same number of free individual discussions with a nurse with regard to recurrence and hospitalization (Chen et al 2019 ). Two trials reported no significant difference in recurrences between a control group and group PE of 16 biweekly sessions (de Barros Pellegrinelli et al 2013 ) or 21 weekly sessions (Morriss et al 2016 ), possibly due to a preponderance of participants with a high number of previous mood episodes.…”
Section: Introductionmentioning
confidence: 99%